2006
DOI: 10.4161/cc.5.22.3473
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Lysine 56 Acetylation: A New Twist in the Chromosome Cycle

Abstract: Several recent reports have identified lysine 56 (K56) as a novel site of acetylation in yeast histone H3. K56 acetylation is predicted to disrupt some of the histone-DNA interactions at the entry and exit points of the nucleosome core particle. This modification occurs in virtually all the newly synthesised histones that are deposited into chromatin during S-phase. Cells with mutations that block K56 acetylation show increased genome instability and hypersensitivity to genotoxic agents that interfere with rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
(113 reference statements)
1
46
0
Order By: Relevance
“…This modification is mediated by histone acetyltransferases (HATs) 7 and is reversible as the acetyl group can be removed through the action of histone deacetylases (HDACs). Lysine acetylation on histones is best characterized for its role in transcriptional regulation, but evidence for a crucial function during replication and DNA damage tolerance is accumulating (1)(2)(3). Indeed, newly synthesized histones that are deposited throughout the genome during replication are transiently acetylated at several lysine residues (4,5).…”
mentioning
confidence: 99%
“…This modification is mediated by histone acetyltransferases (HATs) 7 and is reversible as the acetyl group can be removed through the action of histone deacetylases (HDACs). Lysine acetylation on histones is best characterized for its role in transcriptional regulation, but evidence for a crucial function during replication and DNA damage tolerance is accumulating (1)(2)(3). Indeed, newly synthesized histones that are deposited throughout the genome during replication are transiently acetylated at several lysine residues (4,5).…”
mentioning
confidence: 99%
“…Acetylation of Lys 56 of histone H3 is important for damage tolerance (8), and a recent study has shown that Cul8, Mms1, and Mms22 act downstream of the Lys 56 acetylation pathway (7). Deletion of CUL8, MMS1, MMS22, or ESC4 sen-* This work was supported in part by grants from the Ministry of Education, sitizes the cells to DNA-damaging agents (9 -12).…”
mentioning
confidence: 99%
“…3 One of these special events is the acetylation of histone H3 Lys56 (H3K56) in yeast that has been critically linked to the regulation of genome stability, cell cycle progression and DNA damage responses. 4 H3K56 is strategically placed on the last turn of a core helix-near the convergent entry and exit points of the wrapped DNA, where its acetylation promotes chromatin unfolding. 3,4 The responsible H3K56 HAT in S. cerevisiae [5][6][7][8][9] and S. pombe 10,11 is Rtt109, a novel AcCoA-dependent enzyme that recruits histone chaperones Asf1 or Vps75 for robust H3K56 acetylation.…”
mentioning
confidence: 99%
“…4 H3K56 is strategically placed on the last turn of a core helix-near the convergent entry and exit points of the wrapped DNA, where its acetylation promotes chromatin unfolding. 3,4 The responsible H3K56 HAT in S. cerevisiae [5][6][7][8][9] and S. pombe 10,11 is Rtt109, a novel AcCoA-dependent enzyme that recruits histone chaperones Asf1 or Vps75 for robust H3K56 acetylation. 6,9,11,12 The family relationships of Rtt109 can best be captured by sensitive profile-profile comparison methods such as HHPred 13 that show a distant but significant match to PFAM domain DUF906 (Interpro entry IPR009255) which encompasses the centrally-located HAT domain of p300/CBP orthologs (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation